Cosine and Set-Theoretic Similarity Measures for Generalized Multi-Polar Neutrosophic Soft Set with Their Application in Decision Making - Rana Muhammad Zulqarnain; Aiyared Iampan; Imran Siddique; Hamiden Abd El-Wahed Khalifa (Neutrosophic Sets and Systems, 2022)
A similarity measure and correlation coefficients are used to tackle many issues that include indistinct and blurred information, excluding is not in a position to deal with the general fuzziness and obscurity of the various problems. In this paper, we study some basic concepts which are helpful to build the structure of the article, such as soft set, neutrosophic soft set, and generalized m-polar neutrosophic soft set. The main objective of this paper is to develop the cosine and settheoretic similarity measures for the generalized multipolar neutrosophic soft set (GmPNSS). We discuss some basic operations with their properties for GmPNSS. A decision-making approach has been established by using cosine and set-theoretic similarity measures. Also, we introduce the multipolar neutrosophic soft weighted average (mPNSWA) operator and develop a decisionmaking approach based on mPNSWA. Furthermore, we use to develop techniques to solve multicriteria decision-making problems. Finally, the advantages, effectiveness, flexibility, and comparative analysis of the algorithms are given with prevailing methods.